Long Term Follow-Up Of Patients With Nonrefluxing Hydronephrosis - Yılmaz, Songül; Özçakar, Zeynep Birsin; Cakar, Nilgun; Biral Coşkun, Burcu; Burgu, Berk; Yalcinkaya, Fatoş (Klinische Pädiatrie, 2023)
Backgound The aim of this study is to examine the long-term prognosis of children with ureteropelvic junction obstruction-like hydronephrosis (UPJO-like HN).Patients and Methods The files of children with hydronephrosis (HN) were analyzed retrospectively. Patients with vesicoureteral reflux (VUR) and other genitourinary anomalies were excluded. The final status of the HN, the need for surgery, and urinary tract infection (UTI) frequency were evaluated.Results The study included 219 patients with 302 renal units (RU) with HN. Surgery rate was higher in RUs with larger kidney size and parenchymal thinning (p:<0.001 for both). Hydronephrosis resolved in 113 (40.2%) RUs, improved in 66 (23.3%), unchanged in 100 (35.5%) and worsened in 4 (1.4%). The frequency of recovery and improvement was found to be less in RUs with severe HN, large kidney size, and thin parenchyma. The UTI frequency was higher in severe HN group (12.2% vs 30.6% p:<0.001).Conclusions Children with mild HN had an excellent prognosis. Although the majority of the patients with high-grade HN had also a good prognosis, it seems important to closely follow up patients with severe HN, increased kidney size, and accompanying parenchymal thinning. Clinicians should be aware of the increased frequency of UTIs in children with severe HN.
Keywords: urinary tract infection; ureteropelvic junction obstruction; Hydronephrosis; kidney